If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7cosx + 9 = -2cosx Reorder the terms: 9 + 7cosx = -2cosx Solving 9 + 7cosx = -2cosx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2cosx' to each side of the equation. 9 + 7cosx + 2cosx = -2cosx + 2cosx Combine like terms: 7cosx + 2cosx = 9cosx 9 + 9cosx = -2cosx + 2cosx Combine like terms: -2cosx + 2cosx = 0 9 + 9cosx = 0 Add '-9' to each side of the equation. 9 + -9 + 9cosx = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 9cosx = 0 + -9 9cosx = 0 + -9 Combine like terms: 0 + -9 = -9 9cosx = -9 Divide each side by '9osx'. c = -1o-1s-1x-1 Simplifying c = -1o-1s-1x-1
| t/14=9 | | 0.333X+1.5=1+0.16666X | | -7+9e=7e-11 | | x(x-1)(x+3)=65 | | 8x+8=6x+8 | | 4x+3x=10x | | 214x-742=43x | | 5(x+3)=7+5x | | 3x+5-x=3+2x+2 | | 9e-7=7e-1 | | 4√7/12 | | 0.2222222222222222X-0.1111111111111111=1X-0.2222222222222222 | | 5(3a-3)=3(4a+4) | | t^2-2t-14=0 | | lne^4/9 | | x(3x+2)=7 | | x=15-5*2+1 | | -0.4285714285714286X-0.4285714285714286=-0.8571428571428571-0.1428571428571429X | | 9/2k-2=2/k-8 | | (4/3)(3.14)(36) | | 1+2z-z^2=0 | | 7(3x-4)=x+152 | | 5(4a-8)=140 | | 4x^2-d=2 | | y=-.04x^2+8.5x+4.5 | | 3x+11=7x-23 | | 6(3x-12)=x+115 | | 8/7=-1/-4-k | | 27/81=3/r | | -29=13q-2 | | 6x+2=12x-10 | | y=-13x+45 |